Lignin Modification Leads to Increased Nodule Numbers in Alfalfa. Issue 3 (9th January 2014) - Gallego-Giraldo, Lina; Bhattarai, Kishor; Pislariu, Catalina I.; Nakashima, Jin; Jikumaru, Yusuke; Kamiya, Yuji; Udvardi, Michael K.; Monteros, Maria J.; Dixon, Richard A.
Abstract : Reducing lignin content in stems and roots of alfalfa results in an increased nodule number phenotype . Abstract: Reduction of lignin levels in the forage legume alfalfa ( Medicago sativa ) by down-regulation of the monolignol biosynthetic enzyme hydroxycinnamoyl coenzyme A:shikimate hydroxycinnamoyl transferase (HCT) results in strongly increased digestibility and processing ability of lignocellulose. However, these modifications are often also associated with dwarfing and other changes in plant growth. Given the importance of nitrogen fixation for legume growth, we evaluated the impact of constitutively targeted lignin modification on the belowground organs (roots and nodules) of alfalfa plants. HCT down-regulated alfalfa plants exhibit a striking reduction in root growth accompanied by an unexpected increase in nodule numbers when grown in the greenhouse or in the field. This phenotype is associated with increased levels of gibberellins and certain flavonoid compounds in roots. Although HCT down-regulation reduced biomass yields in both the greenhouse and field experiments, the impact on the allocation of nitrogen to shoots or roots was minimal. It is unlikely, therefore, that the altered growth phenotype of reduced-lignin alfalfa is a direct result of changes in nodulation or nitrogen fixation efficiency. Furthermore, HCT down-regulation has no measurable effect on carbon allocation to roots in either greenhouse or 3-year field trials.